دراسة العلاقة بين تطوّر التجارة الإلكترونية وكلّ من الناتج المحلي الإجمالي والصادرات والواردات في سورية - غدير باسم (Latakia University Journal - Economic and Legal Sciences Series, 2016)
أدّت التطورات التكنولوجية الحديثة إلى تطوير كبير في بيئة الأعمال الإلكترونية(E-Business)، الأمر الذي قاد إلى نشوء مصطلح اقتصاد المعرفة (knowledge economy) كأحد أهم مصطلحات العصر الاقتصادية. تعدّ التجارة الإلكترونية أحد أهم تطبيقات ذلك الاقتصاد، وقد تطوّرت كثيرا في العقد الأخير، يشير إلى ذلك تطور عائداتها في الكثير من دول العالم. تسهم التجارة الإلكترونية في التنمية الاقتصادية من خلال تأثيرها الإيجابي على مجموعة من المؤشرات الاقتصادية كمساهمتها في الناتج المحلي الإجمالي وزيادة الصادرات، من هنا جاء هذا البحث ليدرس فيما إذا كان هناك علاقة بين تطور التجارة الإلكترونية والناتج المحلي الإجمالي وكمية الصادرات والواردات في سورية خلال الفترة الممتدة مابين 2000-2010، حيث تبيّن وجود تلك العلاقة، مع عدم إمكانية الجزم بكونها علاقة سببية في ظلّ الظروف الاقتصادية العامة في سورية خلال تلك الفترة. Recent technological developments have led to a major development in the e-business environment, announcing the emergence of the new term “knowledge economy” as one of the most important economic nomenclatures. E-commerce which is considered as one of the most significant applications of this economy has evolved a lot in the last decade according to the evolution of its revenue in many countries around the world. E-commerce contributes to the economic development through its positive impact on a range of economic indicators such as GDP and export development. The aim of this research is to study whether there was a correlation between the development of electronic commerce and the amount of Syrian exports and imports during the period between 2000 and 2010. The results showed a good correlation between the above mentioned variables, but with no possibility to assert whether it was a causal correlation in the light of general economic conditions in Syria during that period.